A unifying model that explains the origins of human inverted copy number variants. - Bonita J Brewer; Maitreya J Dunham; M K Raghuraman (PLoS Genetics, 2024)
With the release of the telomere-to-telomere human genome sequence and the availability of both long-read sequencing and optical genome mapping techniques, the identification of copy number variants (CNVs) and other structural variants is providing new insights into human genetic disease. Different mechanisms have been proposed to account for the novel junctions in these complex architectures, including aberrant forms of DNA replication, non-allelic homologous recombination, and various pathways that repair DNA breaks. Here, we have focused on a set of structural variants that include an inverted segment and propose that they share a common initiating event: an inverted triplication with long, unstable palindromic junctions. The secondary rearrangement of these palindromes gives rise to the various forms of inverted structural variants. We postulate that this same mechanism (ODIRA: origin-dependent inverted-repeat amplification) that creates the inverted CNVs in inherited syndromes also generates the palindromes found in cancers.